CHARACTERISTICS OF A TRUE PARAMETER OF A HIDDEN MARKOV MODEL - SETIAWATY, B. (School of Data Science, Mathematics and Informatics, IPB University, 2003)
Representation which generates the observed process of a hidden Markov model is not unique. The simplest one, that is, the one with minimum size is called a true parameter. This article is aimed to present characteristics of this parameter.